Complications of Continent Cutaneous Catheterizable Channel in Adult - Vicky Balani, Naveed Ahmed Mahar, Mohsin Mustafa Memon, Farag Mohsen Saleh Abo Ali, Sara Rasheed Kalwar, Murli Lal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the frequency of postoperative complications related to continent cutaneous channel. Study Design: Descriptive study Place and duration of study: Department of Urology, Sindh Institute of Urology & Transplantation, Karachi, Pakistan from 1st August 2019 to 30th November 2021 Methodology: One hundred and seven patients underwent continent catheterizable channel formation via Mitrofanoff principle were included. Each patient was followed in OPD up to 6 months post-procedure to assess the complications i.e. stomal stenosis, stomal incontinence and surgical site infection. Results: Mean age was 31.07±12.78 years. Out of 107 patients, 85(79.4%) were males while 22(20.6%) were females. Postop stenosis was found in 26(24.3%), incontinence in 3(2.8%) while surgical site infection was noted in 48(44.9%) patients. Conclusions: Surgical site infection is the most common postoperative complication that warrants attention followed by stenosis and incontinence.